(untitled) (Archaeologia Adriatica, 2012)
Archaeological investigations are usually focused on areas with the highest concentration of the remains of the material culture of a community, such as the settlements and cemeteries, while landscapes, including the industrial ones, often remain on the margins of research. This is the case with quarries, which testify to the industrial past of an area and provide an insight into social organization of a society in a given period. In the Mediterranean region, including our coast and islands, ancient quarries are numerous, which extend over large areas of landscape, but since many are used in subsequent periods, traces of extraction of raw material from antiquity are often destroyed. Similar is the case with the quarries found in Stari Grad Bay. Along the northern side of the bay there are six locations with visible traces of stone extraction. Extremely large contour lines of the rock suggested that these are ancient quarries from which large blocks were extracted and used in construction of city walls of the Greek Pharos. Multidisciplinary approach to the study of the quarries included using multiple methods of research. Surface surveys were conducted on all six locations, as well as aerial prospection and analysis of historical imagery and cadastral maps. A comparative analysis of the technology of extraction of raw material and micropaleontological analysis of samples from the quarries and city walls were also conducted, and everything was mapped in geographic information system (GIS).